RANCANG BANGUN SISTEM INFORMASI PENDATAAN ADMINISTRASI KEPENDUDUKAN DESA MENGGUNAKAN PENDEKATAN ZACHMAN FRAMEWORK - cecep kurnia sastradipraja; Muhamad Muslih; Rina Hati (INFOKOM (Informatika & Komputer), 2022)
The purpose of this research is to determine how the application of the Zachman Framework in designing a population administration data collection system in Kadaleman village because the current process is still carried out conventionally so that data storage is irregular. In analyzing the system using the Zachman Framework approach with the perspective of Planner, Owner, Designer, and Builder and perspective issues, namely What, How, Where, Who, and When. For system modeling using UML. The data was collected using observation, interviews, literature study, and questionnaires involving 35 respondents. Measurement of data using a Likert scale, with correlation test analysis using Spearman rho. The implementation of a web-based system prototipe with the results of the usability value test in the system application shows that the system has met the aspects of learnability, efficiency, memorability, error, satisfaction. The results of the correlation analysis of the Zachman Framework model on the system built have a very strong correlation, which implies that the system built through the Zachman Framework approach can be realized and implemented.